Scoping Review for a Global Hearing Care Framework: Matching Theory with Practice - Brice, Sophie; Saunders, Elaine; Edwards, Brent (Seminars in Hearing, 2023)
The hearing healthcare industry is evolving rapidly. A framework addressing provision options in contemporary hearing care could assist clinician and client navigate their options to find the most appropriate solution for each individual. A PRISMA approach was used followed by mapping, validation, and thematic analysis to produce a framework to better describe and discuss service and product delivery options in contemporary hearing care. No frameworks were identified to advise matching needs with current provision options in audiological care. Charting, mapping, and thematic analysis of the validation criteria and hearing care literature produced three core domains: Service, Channel, and Technology/Device. The framework developed in this review allows for an understanding of where innovation is occurring in hearing healthcare and differentiates between changes to technology, channel, and service. New questions open up such as whether one model is more effective than another or which model of hearing help is best for which type of person. This framework allows for the disambiguation of hearing health services, hearing loss technology, and the channel in which services and technology are delivered. It has potential to be a versatile and valuable addition to the industry of hearing healthcare.
Keywords: framework; hearing care; devices; self-fit